A collage of environmental history - Sarkar, Mahua (Kolkata: Jadavpur University: Alphabet Books, 2017)
With reference to India.
"Some of the papers of this edited volume were presented in the international seminar, held in February, 2016 in the Department of History, Jadavpur University"--Preliminary page viii.
Includes bibliographical references.
Keywords: HUMAN ECOLOGY-HISTORY; ENVIRONMENTAL HISTORY